RNA-seq Transcriptome Analysis of Panax japonicus, and Its Comparison with Other Panax Species to Identify Potential Genes Involved in the Saponins Biosynthesis - Rai, Amit; Yamazaki, Mami; Takahashi, Hiroki; Nakamura, Michimi; Kojoma, Mareshige; Suzuki, Hideyuki; Saito, Kazuki (Frontiers in Plant Science, 2016)
The Panax genus has been a source of natural medicine, benefitting human health over the ages, among which the Panax japonicus represents an important species. Our understanding of several key pathways and enzymes involved in the biosynthesis of ginsenosides, a pharmacologically active class of metabolites and a major chemical constituents of the rhizome extracts from the Panax species, are limited. Limited genomic information, and lack of studies on comparative transcriptomics across the Panax species have restricted our understanding of the biosynthetic mechanisms of these and many other important classes of phytochemicals. Herein, we describe Illumina based RNA sequencing analysis to characterize the transcriptome and expression profiles of genes expressed in the 5 tissues of P. japonicus, and its comparison with other Panax species. RNA sequencing and de novo transcriptome assembly for P. japonicus resulted in a total of 135,235 unigenes with 78,794 (58.24%) unigenes being annotated using NCBI-nr database. Transcriptome profiling, and gene ontology enrichment analysis for 5 tissues of P. japonicus showed that although overall processes were evenly conserved across all tissues. However, each tissue was characterized by several unique unigenes with the leaves showing the most unique unigenes among the tissues studied. A comparative analysis of the P. japonicus transcriptome assembly with publically available transcripts from other Panax species, namely, P. ginseng, P. notoginseng, and P. quinquefolius also displayed high sequence similarity across all Panax species, with P. japonicus showing highest similarity with P. ginseng. Annotation of P. japonicus transcriptome resulted in the identification of putative genes encoding all enzymes from the triterpene backbone biosynthetic pathways, and identified 24 and 48 unigenes annotated as cytochrome P450 (CYP) and glycosyltransferases (GT), respectively. These CYPs and GTs annotated unigenes were conserved across all Panax species and co-expressed with other the transcripts involved in the triterpenoid backbone biosynthesis pathways. Unigenes identified in this study represent strong candidates for being involved in the triterpenoid saponins biosynthesis, and can serve as a basis for future validation studies.